TRANSFORMATION LEADERSHIP IN THE DIGITAL AGE OF THE SCHOOL ADMINISTRATORS UNDER ROI ET PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Kamsong, Matarak; Chanayotha, Porntiwa (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research were 1) to study the leadership in Digital transformation of educational institution administrators. 2) to compare the of administrators and teachers’ opinions towards the digital transformation leadership of school administrators under Roi Et Primary Educational Service Area Office 2, classified by position, work experience and school size 3) to study the guidelines for development of leadership in the digital age of school administrators under Roi Et Primary Educational Service Area Office 2. The sample group consisted of 338 administrators and teachers, and 5 key informants. The research instrument was a 5-point rating scale questionnaire. The confidence value of the whole issue 0.907 and the interview form was semi-structured. The statistics used were frequency, percentage, mean, and standard deviation. The t-test statistic and the one-way analysis of variance F-test (One-Way ANOVA). The results showed that 1) Leadership level in the digital age of school administrators under the Office of Roi Et Primary Educational Service Area 2, overall, it was at a high level. When considering each aspect, in order of averages from the highest to the lowest were motivational, followed by ideological influence, individual considerations. The side with the lowest average intellectual stimulation. 2) The results of the comparison of the level of opinions of personnel towards the digital transformation leadership of school administrators under the Office of Roi Et Primary Educational Service Area 2, classified by position work experience, and school size. Classified by school size overall and in each aspect no different. 3) Recommendations for the development of leadership in the digital transformation of educational institutes under the Office of Roi Et Elementary Education Area 2, it was found that personnel development should be planned and created guideline for personnel development to determinate a policy for personnel to receive training or online training, to participate and to promote academic development activities in the field of technology development for executives, a good model to support and promote awareness of ethical principles for the evolution of digital social culture in the use of appropriate media.